Kompetensi Kewirausahaan Kepala Sekolah dalam Program Eduprenuership di SMPN 2 Kecamatan Pulung Kabupaten Ponorogo - Ainul Nurhayati Istiqomah; Akhmad Munir (Southeast Asian Journal of Islamic Education Management, 2022)
Abstract This study aims to determine how the entrepreneurial competence of the principal of SMPN 2 Pulung District, Ponorogo Regency based on five main characteristics according to Permendiknas No. 13 of 2007 in the edupreneurship program. This study uses qualitative research through three steps in data analysis, namely data reduction, data display, and data analysis. The results of the study indicate that entrepreneurial competence which is one of the competencies that must be met by school principals which includes five characteristics is very supportive in the edupreneurship program that has been implemented at SMPN 2 Pulung District, Ponorogo Regency. The application of the five characteristics include: first, the creation of innovations that are beneficial for school development, namely the innovation of the edupreneurship program. Second, work hard in achieving school success as a collection of effective learners, namely the principal is always ready to take on task experts in dealing with various problems that arise. Third, a strong motivation to succeed in carrying out his main duties and functions as a leader, namely the principal always provides motivation in every formal and non-formal meeting related to the edupreneurship program. Fourth, never give up and always look for a solution to a problem that arises in the school. Fifth, the entrepreneurial instinct for managing school service production activities as a source of student learning, namely the existence of SMEs or small businesses and the management of cooperatives in the edupreneurship program. The program is run by the school in order to grow young entrepreneurs who are creative, innovative, and able to compete in facing various challenges. Keywords: Entrepreneurship Competence, Eduprenuership